Exploring Satisfaction and Loyalty on Select Monastic Heritage Sites with Special References to Sikkim - Mangar, Urgen; Gachuiwo, Happyson; Dey, Moumita; Lyngdoh, Yoowanka; Awungshi, T Luithuiwung (International Journal of Membrane Science and Technology, 2023)
The study aims to identify factors affecting image and satisfaction on monastic heritage sites. The information is gathered via a methodological survey with 500 respondents who visited select monastic heritage sites. Out of 500 respondents,425 respondents’ data were used in this study. The study has identified five factors that influence Tourists’’’ Satisfaction I.e. Culture heritage sites, Perceive value, Service quality, Image, and Environment. The study had a theoretical framework Confirmatory factor analysis is used for model fit. The study hypotheses have been verified by using structural equation modeling. Moreover, image, satisfaction, and Loyalty found a strong linkage among the constructs. Therefore, this study is limited to select Monastic heritage sites of the east district, Sikkim (Gangtok).